REVIEW 10 PENELITIAN TENTANG PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA PARA MANAJER - Eksa Ridwansyah; Yuliansyah , (Media Riset Akuntansi, Auditing & Informasi, 2010)
This article is to review of ten researches in Indonesia which discussed the influency of budgeting participation toward the managerial performance. This article founds some variation of samples, methods, and conclusions of these researches. Ten researches are purposively selected with two conditions, the studies were conducted in Indonesia and after 2000. Based on the general review, these ten researches resulted vary conclusions, depended on the research variables. Nevertheless, most of researches found that budgeting participation affected managerial performance.